0464 Prevalence Of Sleep-disordered Breathing After Stroke And Transitory Ischemic Attack: A Meta-analysis. (27th April 2018) - Seiler, A; Camilo, M; Korostovtseva, L; Haynes, A G; Brill, A; Horvath, T; Egger, M; Bassetti, C L
Abstract: Introduction: A meta-analysis of 29 studies (2343 patients) in 2010 suggested a high prevalence of SDB after stroke. The objective of this study was to perform a new meta-analysis on the prevalence of SDB and to assess its evolution in time. Methods: We systematically searched the electronic databases PubMed, Embase, the Cochrane Library, and CINAHL from their commencements to April 2017 for clinical studies reporting on the prevalence and/or severity of SDB in ischemic and hemorrhagic stroke as well as TIA. We included studies using full polysomnography or diagnostic devices of the AASM categories I-IV. PROSPERO registration number: CRD42017072339. Results: 89 out of the 5211 identified studies with 7096 patients met the inclusion criteria. 54 studies were performed in the acute phase after stroke (<1 month after stroke), 23 studies in the subacute phase (after 1–3 months) and 12 studies in the chronic phase (> 3 months). In 41 studies full polysomnography was used. The mean AHI was 26/h (SD 22–31) and comparable in ischemic stroke, hemorrhagic stroke and TIA. Obstructive apneas (mean value 12/h) were more common than hypopneas (9/h) and central apneas (5/h). An AHI> 5/h and >30/h was found in 71% and 30% of patients, respectively. The severity of SDB was similar in all phases after stroke; however, only three studies assessed the same patients over time. Frequency and severity of SDB did not vary according to diagnostic device used. Data on predictors of SDB were scarse/non conclusive. Conclusion: Almost 1/3 of stroke patients present severe SDB, which appears to persist over time. Portable respirographies are accurate to assess SDB in this setting. The impact of stroke characteristics on severity and type of SDB remains uncertain. Support (If Any): Swiss National Science Foundation grants 320030-149752 and 320030-125069.